2018
DOI: 10.1172/jci.insight.99680
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin/T-cadherin system enhances exosome biogenesis and decreases cellular ceramides by exosomal release

Abstract: Adiponectin, an adipocyte-derived circulating protein, accumulates in vasculature, heart, and skeletal muscles through interaction with a unique glycosylphosphatidylinositol-anchored cadherin, T-cadherin. Recent studies have demonstrated that such accumulation is essential for adiponectin-mediated cardiovascular protection. Here, we demonstrate that the adiponectin/T-cadherin system enhances exosome biogenesis and secretion, leading to the decrease of cellular ceramides. Adiponectin accumulated inside multives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
164
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(184 citation statements)
references
References 74 publications
(91 reference statements)
9
164
0
Order By: Relevance
“…Toxic sphingolipids such as sulfatides or psychosine have been shown to accumulate in some sphingolipidoses and to be secreted with EVs . The cellular ceramide content has also been shown to be regulated by exosome secretion through adiponectin binding to T‐cadherin . Adiponectin is a protein secreted by adipocytes as oligomers that bind to T‐cadherin, a unique GPI‐anchored form of cadherin notably present in lipid rafts of endothelial vascular cells.…”
Section: Exosomes and Homeostasismentioning
confidence: 99%
See 1 more Smart Citation
“…Toxic sphingolipids such as sulfatides or psychosine have been shown to accumulate in some sphingolipidoses and to be secreted with EVs . The cellular ceramide content has also been shown to be regulated by exosome secretion through adiponectin binding to T‐cadherin . Adiponectin is a protein secreted by adipocytes as oligomers that bind to T‐cadherin, a unique GPI‐anchored form of cadherin notably present in lipid rafts of endothelial vascular cells.…”
Section: Exosomes and Homeostasismentioning
confidence: 99%
“…118,119 The cellular ceramide content has also been shown to be regulated by exosome secretion through adiponectin binding to Tcadherin. 120 Adiponectin is a protein secreted by adipocytes as oligomers that bind to T-cadherin, a unique GPI-anchored form of cadherin notably present in lipid rafts of endothelial vascular cells. It was shown that high molecular weight multimeric adiponectin accumulates in MVE ILVs, stimulates exosome biogenesis and exosomal release of ceramides, with a concomitant reduction in cellular ceramides both in vitro and in vivo.…”
Section: Lipidsmentioning
confidence: 99%
“…This group showed exosome release is attenuated after inhibition of the sphingomyelin (SM) hydrolyzing enzyme neutral sphingomyelinase . Obata et al showed cellular CER levels decreased when adiponectin mediated increase in exosome biogenesis and secretion occurs …”
Section: Introductionmentioning
confidence: 99%
“…26 Obata et al showed cellular CER levels decreased when adiponectin mediated increase in exosome biogenesis and secretion occurs. 27 Urinary lipidomics, in general, has become an attractive area in biomedical sciences since the urine is a rich source of non-invasive biomarkers and it can be used to investigate disease mechanisms. Lipidomics of urinary exosomes may offer an additional advantage because the packaged cargo within these urinary exosomes may be associated with alterations in various cellular processes including signaling, differentiation, and communication.…”
mentioning
confidence: 99%
“…The ability of adiponectin to reduce tissue ceramide levels has been posited to explain its insulin sensitizing and anti-inflammatory properties (11)(12)(13). Adiponectin also has been shown to bind a separate GPI-linked receptor T-cadherin (14), which has recently been shown to also reduce tissue ceramide levels by triggering the release of exosomes (15). These findings together suggest a role for adiponectin in ameliorating metabolic disease by altering tissue lipids, especially ceramides, via receptor binding and activation of downstream intracellular processes.…”
Section: Introductionmentioning
confidence: 99%